Yeast and yeast‐like fungi associated with dry indehiscent fruits of Nothofagus nervosa in Patagonia, Argentina - Fernandez, Natalia Verónica; Mestre, María Cecilia; Marchelli, Paula; Fontenla, Sonia Beatriz (Oxford Academic Press, 2019)
Nothofagus nervosa (Raulí) is a native tree species that yields valuable timber. It was overexploited in the past and is currently included in domestication and conservation programs. Several research programs have focused on the characterization of epiphytic microorganisms because it has been demonstrated that they can affect plant–pathogen interactions and/or promote plant growth. Although the microbial ecology of leaves has been well studied, less is known about microorganisms occurring on seeds and noncommercial fruits. In this work, we analyzed the yeast and yeast‐like fungi present on N. nervosa fruits destined for the propagation of this species, as well as the effects of fruit preservation and seed dormancy‐breaking processes on fungal diversity. Morphological and molecular methods were used, and differences between fungal communities were analyzed using a similarity index. A total of 171 isolates corresponding to 17 species were recovered, most of which belong to the phylum Ascomycota. The majority of the species develop mycelia, produce pigments and mycosporines, and these adaptation strategies are discussed. It was observed that the preservation process considerably reduced yeast and yeast‐like fungal diversity. This is the first study concerning microbial communities associated with this ecologically and economically important species, and the information presented is relevant to domestication programs.